2017
DOI: 10.1021/acs.inorgchem.6b02073
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Behavior of the Z Bonds in X–Z···Y Weak Interactions: Z = Main Group Elements Versus the Transition Metals

Abstract: In contrast to the increasing family of weak intermolecular interactions in main-group compounds (X-Z···Y, Z = main-group elements), an analysis of the Cambridge Structural Database indicates that electron-saturated (18-electron) transition-metal complexes show reluctance toward weak M bond formation (X-M···Y, M = transition metal). In particular, weak M bonds involving electron-saturated (18-electron) complexes of transition metals with partially filled d-orbitals are not found. We propose that the nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 104 publications
1
28
0
Order By: Relevance
“…We propose herein to name these bonds "spodium bonds" because a derivative of the first element of the group (ZnO) is called spodium in Latin. It is important to emphasize that the interesting and remarkable work of Joy and Jemmis [76] anticipated that metals of the twelfth group might also participate in noncovalent interactions as Lewis acids. Moreover, these authors also showed that for groups 3-10, this type of interaction (denoted generically as metal bonding) is very scarce.…”
Section: Spodium Bondsmentioning
confidence: 99%
“…We propose herein to name these bonds "spodium bonds" because a derivative of the first element of the group (ZnO) is called spodium in Latin. It is important to emphasize that the interesting and remarkable work of Joy and Jemmis [76] anticipated that metals of the twelfth group might also participate in noncovalent interactions as Lewis acids. Moreover, these authors also showed that for groups 3-10, this type of interaction (denoted generically as metal bonding) is very scarce.…”
Section: Spodium Bondsmentioning
confidence: 99%
“…Among the great deal of noncovalent forces, investigations on σ-hole interactions [ 4 , 5 ] are growing very fast and are definitively recognized by the scientific community as an alternative to the ubiquitous hydrogen bonding [ 6 ]. Very recently, the attractive interaction between elements of Group 12 of the Periodic Table and any electron rich ‘accepting’ atom (:A) [ 7 , 8 ] has been termed as a spodium bond (SpB) [ 9 ]. Therefore, the SpB has become a new member of the σ-hole family of interactions and it is adequate to differentiate the coordination bond (high covalent character) typical of transition metals from the noncovalent contact.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that the location of the σ‐holes in Pt and Au NPs seemed to be correlated with their catalytic activity. Recently, inspection of the CSD by Joy et al., backed up by theoretical calculations, revealed the participation of pentacoordinate transition metal complexes in noncovalent Cl−M ⋅⋅⋅ Y (M=Co, Rh, Ir; Y=electron‐rich atom) interactions. In addition, Stenlid et al.…”
Section: Introductionmentioning
confidence: 99%